Analysis of cytokine response characteristics and immunopathogenetic effects of double-stranded sodium salt RNA-based drug for postexposure prophylaxis against novel coronavirus infection: double-blind, placebo-controlled trial - O. A. Radaeva; L. A. Balykova; K. Ya. Zaslavskaya; Yu. A. Kostina; N. A. Pyataev; N. M. Selezneva; A. V. Klimova; I. Yu. Chegodaeva; K. N. Koryanova; A. V. Taganov; P. A. Bely (Фармация и фармакология (Пятигорск), 2023)
The aim of the work was to study сytokine response characteristics in the group of persons contacted by a novel coronavirus infection depending on the development of the disease over the next 14 days. Herewith, for the immunocorrection with a preparation based on RNA double-stranded sodium salt (RADAMIN®VIRO) causing a secondary reduction in the risk of COVID-19 in the analyzed group, potential targets had been selected.Materials and methods. A double-blind, placebo-controlled study of the drug based on RNA double-stranded sodium salt therapeutic effects was conducted in a group of patients who had been in contact with the persons having a confirmed diagnosis of COVID-19. The method of enzyme immunoassay in dynamics was used to determine the content of interferons alpha and beta (IFNα and IFNβ, respectively), interleukin-1β and -10 (IL1β and IL-10, respectively) in the blood serum and saliva in the contact persons, with a retrospective assessment of changes depending on the administration of the drug or placebo, as well as the development of COVID-19.Results. In the course of the presented study, it was demonstrated that the established content of IFNα (less than 28 pg/ml) and IFNβ (less than 12 pg/ml) in saliva on the 1st–2nd contact days is a predictor of an increased risk of developing COVID-19. Herewith, the increase degree in these immunoregulatory peptides in the interval of 2–3 contact days is important: IFNα and IFNβ allows leveling the negative prognosis in patients by 250% or more. The lowest rates (p <0.001) of INFα on the 1st–2nd contact days, as well as an increase of less than 21% by the 3rd day, were observed in persons with a waist circumference of more than 80/94 cm (women/men). The incidence in this group was higher and amounted to 85% (16 out of 20 people). The predictor role of IL-1β and IL-10 in the blood and saliva in relation to the start of the infectious process was not revealed. The administration of drug based on RNA double-stranded sodium salt to the contact patients made it possible to correct the interferon response in the form of an increase in the content of IFNα and IFNβ, as well as to reduce the incidence in comparison with the placebo group.Conclusion. Differences in the interferon regulation upon contact with SARS-CoV-2 in the form of lower INF α and β levels, as well as a slightly pronounced growth dynamics in the interval of the first 3 days, influenced the increased risk of developing COVID-19. RADAMIN®VIRO can be recommended as a means of post-exposure prophylaxis of COVID-19 for both medical institutions and for caregivers and / or contacts with COVID-19 patients.